Skip to content
Related Articles
Get the best out of our app
GFG App
Open App
geeksforgeeks
Browser
Continue

Related Articles

Class 10 NCERT Solutions – Chapter 2 Polynomials – Exercise 2.2

Improve Article
Save Article
Like Article
Improve Article
Save Article
Like Article

Question 1. Find the zeroes of the following quadratic polynomials and verify the relationship between the zeroes and the coefficients.

(i) x2 – 2x – 8

x2 – 2x – 8 = x2 – 4x + 2x – 8 

= x (x – 4) + 2(x – 4) 

= (x – 4) (x + 2)

Therefore, zeroes of equation x2 – 2x – 8 are (4, -2)

Sum of zeroes is equal to [4 – 2]= 2 = -(-2)/1 

i.e. = -(Coefficient of x) / (Coefficient of x2)

Product of zeroes is equal to 4 × (-2) = -8 =-(8)/1  

i.e.= (Constant term) / (Coefficient of x2)

(ii) 4s2 – 4s + 1

4s2 – 4s + 1 = 4s2 – 2s – 2s +1 

= 2s(2s – 1) – 1(2s – 1) 

= (2s – 1) (2s – 1)

Therefore, zeroes of  equation 4s2 – 4s +1 are (1/2, 1/2)

Sum of zeroes is equal to [(1/2) + (1/2)] = 1 = -4/4 

i.e.= -(Coefficient of s) / (Coefficient of s2)

Product of zeros is equal to [(1/2) × (1/2)] = 1/4 

i.e.= (Constant term) / (Coefficient of s2 )

(iii) 6x2 – 3 – 7x

6x2 – 3 – 7x = 6x2 – 7x – 3 

= 6x2 – 9x + 2x – 3 

= 3x(2x – 3) + 1(2x – 3) 

= (3x + 1) (2x – 3)

Therefore, zeroes of equation 6x2 – 3 – 7x are (-1/3, 3/2)

Sum of zeroes is equal to -(1/3) + (3/2) = (7/6) 

i.e.= -(Coefficient of x) / (Coefficient of x2)

Product of zeroes is equal to -(1/3) × (3/2) = -(3/6) 

i.e.= (Constant term) / (Coefficient of x2 )

(iv) 4u2 + 8u

4u2 + 8u = 4u(u + 2)

Therefore, zeroes of equation 4u2 + 8u are (0, -2).

Sum of zeroes is equal to [0 + (-2)] = -2 = -(8/4)

i.e. = -(Coefficient of u) / (Coefficient of u2)

Product of zeroes is equal to 0 × -2 = 0 = 0/4 

i.e. = (Constant term) / (Coefficient of u2 )

(v) t2 – 15

 t2 – 15

⇒ t2 = 15 or t = ±√15

Therefore, zeroes of equation t2 – 15 are (√15, -√15)

Sum of zeroes is equal to [√15 + (-√15)] = 0 = -(0/1) 

i.e.= -(Coefficient of t) / (Coefficient of t2)

Product of zeroes is equal to √15 × (-√15) = -15 = -15/1 

i.e. = (Constant term) / (Coefficient of t2 )

(vi) 3x2 – x – 4

3x2 – x – 4 = 3x2 – 4x + 3x – 4

= x(3x – 4) + 1(3x – 4) 

= (3x – 4) (x + 1)

Therefore, zeroes of equation 3x2 – x – 4 are (4/3, -1)

Sum of zeroes is equal to (4/3) + (-1) = (1/3) = -(-1/3) 

i.e. = -(Coefficient of x) / (Coefficient of x2)

Product of zeroes is equal to (4/3) × (-1) = (-4/3) 

i.e. = (Constant term) / (Coefficient of x2)

Question 2. Find a quadratic polynomial each with the given numbers as the sum and product of its zeroes respectively.

(i) 1/4, -1

Let two zeroes be α, β

∴ Sum of zeroes = α + β

∴ Product of zeroes = αβ

Given, Sum of zeroes = α + β = 1/4

Product of zeroes = α β = -1

∴ If α and β are zeroes of any quadratic polynomial, then the quadratic polynomial equation can be written directly as:-

x2 – (α + β)x + αβ = 0

x2 – (1/4)x +(-1) = 0

4x2 – x – 4 = 0

∴ 4x2 – x – 4 is the quadratic polynomial.

(ii) √2, 1/3

Let two zeroes be α, β

∴ Sum of zeroes = α + β

∴ Product of zeroes = αβ

Given Sum of zeroes = α + β =√2

Product of zeroes = αβ = 1/3

∴ If α and β are zeroes of any quadratic polynomial, then the quadratic polynomial equation can be written directly as:

x2 – (α + β)x + αβ = 0

x2 – (√2)x + (1/3) = 0

3x2 – 3√2x + 1 = 0

∴ 3x2 – 3√2x + 1 is the quadratic polynomial.

(iii) 0, √5

Let two zeroes be α, β

∴ Sum of zeroes = α + β

∴ Product of zeroes = αβ

Given, Sum of zeroes = α + β = 0

Product of zeroes = αβ = √5

∴ If α and β are zeroes of any quadratic polynomial, then the quadratic polynomial equation can be written directly as:-

x2 – (α + β)x + αβ = 0

x2 – (0)x + √5 = 0

∴ x2 + √5 is the quadratic polynomial.

(iv) 1, 1

Let two zeroes be α, β

∴ Sum of zeroes = α + β

∴ Product of zeroes = αβ

Given, Sum of zeroes = α + β = 1

Product of zeroes = αβ = 1

∴ If α and β are zeroes of any quadratic polynomial, then the quadratic polynomial equation can be written directly as:-

x2 – (α + β)x + αβ = 0

x2 – x + 1 = 0

∴ x2 – x + 1 is the quadratic polynomial.

(v) -1/4, 1/4

Let two zeroes be α, β

∴ Sum of zeroes = α + β

∴ Product of zeroes = αβ

Given, Sum of zeroes = α + β = -1/4

Product of zeroes = α β = 1/4

∴ If α and β are zeroes of any quadratic polynomial, then the quadratic polynomial equation can be written directly as:-

x2 – (α + β)x + αβ = 0

x2 – (-1/4)x + (1/4) = 0

4x2 + x + 1 = 0

∴ 4x2 + x + 1 is the quadratic polynomial.

(vi) 4, 1

Let two zeroes be α, β

∴ Sum of zeroes = α + β

∴ Product of zeroes = αβ

Given, Sum of zeroes = α + β = 4

Product of zeroes = αβ = 1

∴ If α and β are zeroes of any quadratic polynomial, then the quadratic polynomial equation can be written directly as:

x2 – (α + β)x + αβ = 0

x2 – 4x + 1 = 0

∴ x2 – 4x + 1 is the quadratic polynomial.

My Personal Notes arrow_drop_up
Last Updated : 25 Feb, 2021
Like Article
Save Article
Similar Reads
Related Tutorials